LATIHAN PLYOMETRICS TERHADAP HASIL SHOOTING KE GAWANG SEPAK BOLA EKSTRAKURIKULER SMAN 9 PONTIANAK - Japari Japari; Ahmad Atiq; Mimi Haetami (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2020)
AbstractThe problem discussed in this study is whether there is an effect of plyometrics training on the results of soccer shooting in high school 9 Pontianak students. The purpose of this study was to determine the effect of plyometrics training on the results of soccer shooting in high school 9 Pontianak students.The experimental research method involves two variables, namely the plyometrics exercise independent variable and the dependent variable, the result of soccer shooting. the population of extracurricular soccer students at SMA Negeri 9 Pontianak was 35 students, the sample was taken using the random sampling method, the researcher took all of the population, with a sample of 35 students. This research technique uses tests and measurements, which is a test with a measurement shooting instrument grille in a soccer game. Data analysis using t-test formula. The results of this study indicate that there is an influence of plyometrics training on the results of shooting soccer on the students of SMA Negeri 9 Pontianak. This can be proven based on the results of calculations, where the ttest value is 5.604> ttable value (1.688), so that the alternative hypothesis (Ha) is accepted and the null hypothesis (Ho) is rejected. This means that there is an influence of plyometrics exercises on the results of shooting soccer on the students of SMA Negeri 9 Pontianak Keywords: Plyometrics Training, Shooting